Analyzing the Online Marketplaces of Bangladesh - Amin, Md. Iftekharul; Farjana, Sadia; Bashar, Syeda Mahrufa (AIUB Journal of Business and Economics, 2016)
The online marketplaces have not built up as a structured industry in Bangladesh. But there remains demand for such facilitated marketplaces in this era of busy schedules and severe traffic clogging in the roads. Hence online marketplaces have gained popularity and prosperity here despite their unstructured business frame and poor, inconsistent service. This study focuses on analyzing the Online Marketplaces of Bangladesh elaborately. The online marketplaces in Bangladesh consist of both local and multinational organizations, but there hardly exists proper customer service or rules/guidelines for service offering. A few marketplaces have sustained as trustworthy, dependable hubs for online shoppers, but most of these have mushroomed just capitalizing the easy set-up procedure of online marketplaces. Though online marketplace concept got introduced in Bangladesh in 2005, there has not been much development in the qualitative area for such marketplaces.